EMISSION DISCLOSURE AND MARKET VALUE ADDED OF OIL AND GAS FIRMS IN NIGERIA - O. Okike, Celestine; G Nwachukwu, Ifeoma; A. Agbiogwu, Andrew (African Journal of Social and Behavioural Sciences, 2024)
This study assessed the nexus between emission disclosure and the market value added of quoted oil and gas firms in Nigeria for the period of eleven (11) years spanning from 2012 - 2022. Carbon Disclosure, Nitrogen Oxides Disclosure, and Sulphur Oxides Disclosure were used to proxy Environmental Disclosure whereas Market Value Added served as the dependent variable. In line with the objectives of the study, three hypotheses were formulated. An ex-post facto research design was employed. Six (6) quoted oil and gas firms constituted the sample size of this study. The secondary data were extracted from the annual reports and accounts of the sampled firms and were analysed via E-Views 9.0 statistical software and Panel Least Square (PLS) regression analysis. Findings from the empirical analysis revealed that there is a significant relationship between Carbon Disclosure, Nitrogen Oxides Disclosure and Sulphur Oxides Disclosure and Market Value Added of quoted oil and gas firms in Nigeria at the 5% level of significance. Inter alia, firms should take the issue of emission disclosure seriously to increase the confidence of the public in their operations which translates to healthy the performance of the industry, and relevant agencies in Nigeria should strengthen their monitoring and oversight functions on the compliance level of firms with environmental frameworks.